THE EFFECT OF PROCESS ORIENTED GUIDED INQUIRY LEARNING (POGIL) MODEL ON SCIENCE PROCESS SKILLS (SPS) AND STUDENTS' COGNITIVE ABILITIES ON THE CONCEPT OF REACTION RATE - Said Idrus; Mahmud Mahmud; Zainuddin Muchtar (Chimica Didactica Acta, 2021)
This study aims to determine the effect of the Process Oriented Guided  Inquiry Learning (POGIL) model on Science Process Skills (SPS), cognitive abilities and the correlation between SPS and students' cognitive abilities on the reaction rate concept. The sample in this study were 35 students of class XI SMA Negeri Seribu Bukit 2016-2017 academic year. The data was collected through observation and test. 20 multiple choice questions (alpha:0.81) were used to collect data of student’s SPS. While students' cognitive abilities were obtained by pre-test and post-test using 20 multiple choice questions (alpha:0.84). The distributed normally and homogeneously. The hypothesis was tested by using Paired Sample t-Test at a significance level of 0.05. Based on the data analysis and hypothesis testing carried out, there was a significant difference in the effect of the POGIL model on Science Process Skills (SPS), cognitive abilities and significant interactions between SPS and students' cognitive abilities on the material reaction rate, indicated by the value of each probability or sig. 0,000, so it can be concluded that the results of testing the hypothesis reject Ho or accept Ha at the 5 percent alpha level.